Fracture location impacts opioid demand in upper extremity fracture surgery. Issue 8 (August 2021) - Cunningham, Daniel J.; LaRose, Micaela A.; Anakwenze, Oke A.; Klifto, Christopher S.; Richard, Marc J.; Ruch, David S.; Gage, Mark J.
Highlights: This study focused on the impact of upper extremity fracture location on 90-day and 1-year perioperative outpatient opioid demand In upper extremity fracture surgery, patients filled an average of 88.3 oxycodone 5-mg pills in the 90-day perioperative time frame. 54.7% of patients filled two or more prescriptions in the 90-day perioperative time frame. Fixation of proximal humerus, humeral shaft, distal humerus, and elbow fractures was associated with the greatest increase in opioid demand. Abstract: Introduction: Opioid sparing protocols should be formulated with appropriate demand. Specific fracture location has been hypothesized as an important predictor of post-operative pain. The purpose of this study is to evaluate the impact of fracture location on perioperative opioid demand after surgery with the hypothesis that this factor would be significantly associated with perioperative opioid demand in upper extremity fracture surgery. Methods: A national database was used to identify1-month pre-operative to 1-year postdischarge opioid demand in oxycodone 5-mg equivalents in 336, 493 patients undergoing fracture fixation of the clavicle through distal radius between 2010 and 2020. Three timeframes were evaluated: 1-month pre-op to 90-days post-discharge, 3 months post-discharge to 1-year post-discharge, and 1-month pre-op to 1-year postdischarge. Multivariable main effects linear and logistic regression models were constructed to evaluate the changes in opioids filled, opioid prescriptions, and odds of two or more opioid prescriptions in these timeframes based on fracture location with adjustment for age, sex, obesity, pre-operative opioid usage, and polytrauma. Results: Compared to distal radius fracture fixation, fixation of elbow, distal humerus, humeral shaft, and proximal humerus fractures were associated with large, significant increases in 1-month pre-op to 1-year post-discharge opioid filling (33.5 – 63.4 additional oxycodone 5-mg equivalents, all p<0.05) and number of filled prescriptions (0.33 – 0.92 additional prescriptions, all p<0.05) compared to patients with other operatively treated upper extremity injuries. Discussion: Fracture location was a significant predictor of perioperative opioid demand. Elbow, distal humerus, humeral shaft, and proximal humerus fracture fixation was associated with the largest increases in opioid demand after upper extremity fracture fixation. Patients with these injuries may be at highest risk of extensive opioid consumption. Level of evidence: Level III, retrospective, observational cohort study